A northern light in Provence : a novel - Oberbeck, Elizabeth Birkelund (Ballantine Book, 2024)
" Ilse Lund is a French translator who lives in a beach house on stilts set on a remote spit of land off the west coast of Greenland. Restless from from the predictability of life in her quaint cottage and her isolated world circumscribed by the sea, Ilse convinces her French publisher to pay for a trip to the country whose language she translates but has never visited--France. Her mission: to translate the verses of an elderly Provençal poet known as "the last living troubadour of Provence." Settling into the poet's medieval village of Beau Riviere, perched atop the rocky slopes of the French Alps, Ilse falls under the hypnotic spell of the Provençal way of life--and of the free-associating, charming, French poet. As she soaks up the sensuous warm air, the vibrant spring colors, and the dulcet sounds of the Provençal dialect, a daily rhythm develops, word-by-word, between the poet and his translator. Their warm camaraderie is disturbed, however, when the poet's son shows up. Though he has a fiancée back in Paris, he turns his full attention on Ilse, and suddenly she is forced to learn another language, one her translation skills have not prepared her to decode. Questioning where and with whom her future lies, Ilse fears she has lost sight of her true North."--